Formação docente e qualidade educacional: sentidos discursivos de discentes de Pedagogia da FE/UFG - Oliveira, Anne Cristina Camilo de (2018)
This work is related to the development of a dissertation linked to the research line "Training, Teaching Professionalization and Educational Practices" of the Graduate Program in Education of the Faculty of Education of the Federal University of Goiás, a member of the work developed by Redecentro - Rede de Researchers from the Midwest. Methodologically, the dialectical historical materialistic method was adopted in the development of a case study, with a qualitative approach, whose object of investigation are the discursive meanings on teacher training and educational quality of the students. The research was developed with students of the FE / UFG Pedagogy course (initials and finalists) who answered the following question: what are the discursive meanings about teacher education and educational quality among FE / UFG Pedagogy students? What epistemological perspectives do they reveal? In order to reach our objective, the theoretical problems of the contemporary university, educational policies and their influences in the formation and definition of the quality of education were discussed theoretically. The discursive meanings were collected through questionnaires and analyzed according to Tello's (2013) approach to highlight the epistemological and political perspective of speeches. The results showed that there is a prevalence among them of conceptions of teacher formation aligned with the critical perspective that, in turn, corresponds to the epistemology of praxis, however, in relation to the educational quality was observed another movement, to which stood out the conception of hegemonic quality that corresponds to that present in the discourses linked by the educational policies, to which they support the neoliberal logic defended by the Multilateral Organizations. The superficiality of the discourses, contradictions and imprecision in the expositions of the students, indicating the need for greater investment in training, was also evidenced. In relation to the discursive meanings related to quality, the same movement was observed. As an alternative to this reality, it is proposed that in its formation students should join the struggle for social quality, committing themselves to the human being in their integral formation, from the individual and social dimension. In this sense, it is understood that the discourses of the students could be added to the discussions about the emancipating formation of teachers and social educational quality and thus to provide subsidies for future researches and pedagogical actions, especially when considering the course of Pedagogy / FE / UFG.